WOMEN'S EMPOWERMENT UNDER SULABH MOVEMENT (International Journal of Food and Nutritional Sciences, 2022)
The “Millennium Development Goal (MDG)” for the year 2022 was to decrease in half the number of people who lacked access to basic sanitation, from 2.6 billion at the beginning of the 21st century to 1.1 billion by the end of the same year. This would bring the total number of people without access to basic sanitation down from 2.6 billion. Because of this, the total number of individuals who lacked access would increase to 2.6 billion. As a direct response to the “Millennium Development Goals (MDG)”, Sulabh has made it his personal goal to include every member of the community as an active participant in the movement to reduce the prevalence of poverty and enhance the quality of sanitation. The mission of the organisation was to "achieve a healthy and hygienic India, free of the practise of defecating in the open and the feculent pollution of the environment," as stated in their mission statement. It is not the norm for people to live in communities where they will not give you funny glances if you pick up human faeces by hand, which is sometimes referred to as scavenging. This is because scavenging is becoming increasingly common. In order for Sulabh to fulfil its objective and live up to its vision, the organisation has been devoting a significant amount of effort towards educating and inspiring the general public, raising awareness among policymakers and public employees, and lending support to the efforts of the government and public projects. The women sanitation and empowerment is among the key issues of India and thus, Sulabh has particularly focue on those issues.